Modified MOFs filler, preparation method and composite solid electrolyte of lithium ion battery

By introducing modified MOFs fillers into the electrolytes of lithium-ion batteries, the problems of flammability of liquid electrolytes and insufficient polymer electrolyte performance in lithium-ion batteries are solved, and high conductivity, wide electrochemical window and excellent battery performance are achieved.

CN119552376AActive Publication Date: 2025-03-04NANJING TECH UNIV

Patent Information

Application Number
CN202411583710.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-03-04
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

The liquid electrolytes used in existing lithium-ion batteries have a risk of flammability, and the high crystallinity of polymer electrolytes at room temperature leads to poor conductivity, poor mechanical properties at high temperatures, and narrow electrochemical windows, limiting their application in high voltage solid-state batteries.

Method used

Using modified MOFs fillers, by replacing some metal nodes with cerium in the MIL series MOF materials or performing surface etching treatment, MOF materials with high Lewis acidity were prepared, and combined with the PEO matrix to form a composite solid electrolyte.

Benefits of technology

The conductivity and Li+ transfer number of the composite solid electrolyte are significantly improved, the electrochemical stability window is expanded, the mechanical strength and thermal stability are enhanced, the formation of lithium dendrites is reduced, and the discharge capacity and Coulomb efficiency of lithium batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552376A_ABST
    Figure CN119552376A_ABST
Patent Text Reader

Abstract

The invention discloses a modified MOFs filler, a preparation method and a composite solid electrolyte of a lithium ion battery, and the preparation method of the modified MOFs filler comprises the following steps: adding cerium salt during preparation of an MOF material to obtain a cerium-doped MOF material; or after the MOF material is prepared, the MOF material is etched, and the etched MOF material is obtained. The preparation method of the composite solid electrolyte comprises the following steps: dispersing the prepared MOF material in a solvent under the protection of inert gas, adding an electrolyte lithium salt and PEO, stirring to obtain a colloidal suspension, pouring the colloidal suspension into a mold, and drying and molding. After the obtained modified MOFs filler is added into the composite solid electrolyte, the conductivity of the composite solid electrolyte can be effectively improved, the composite solid electrolyte has a wide electrochemical stability window, and an assembled lithium ion battery shows excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a modified MOFs filler, a preparation method and a composite solid electrolyte of a lithium ion battery, belonging to the technical field of solid battery materials. Background Art

[0002] Lithium-ion battery is a chemical power source that stores and releases energy through the reversible insertion and removal of lithium ions between positive and negative electrode materials. Since the concept of lithium-ion battery was proposed in the late 1970s and Sony successfully commercialized it in 1991, this battery has become the preferred energy storage device in many fields such as portable electronic devices, electric vehicles and large-scale energy storage systems due to its significant advantages such as high energy density, long life and low self-discharge rate. As one of the world's largest lithium-ion battery producers, China has established a complete industrial chain from raw material mining and processing to battery manufacturing and application promotion.

[0003] However, the liquid electrolytes currently used in lithium batteries are flammable and may cause battery overheating and lead to safety accidents. The continued development of battery technology requires not only the improvement of energy density and cycle stability, but also the urgent need to solve safety issues to achieve comprehensive optimization of lithium-ion battery technology. Compared with traditional liquid electrolyte lithium batteries, all-solid-state lithium batteries have higher safety, longer cycle life and higher energy density, becoming an effective strategy for balancing high safety and high specific energy, and an effective means to solve the above safety issues.

[0004] Solid electrolytes are solid substances with ionic conductivity named after liquid electrolytes. At present, solid electrolytes can be divided into three types according to material properties: inorganic electrolytes, polymer electrolytes and composite electrolytes. In the 1970s, the concept of polymer electrolytes (PEs) was first proposed, and then it was tried to be applied to lithium-ion batteries, and the research and development of polymer electrolytes in lithium-ion batteries began. Compared with inorganic solid electrolytes, polymer electrolytes are easier to process, lighter and cheaper. At the same time, due to their high flexibility, they can buffer the volume expansion of the electrode to a certain extent during the battery cycle, which is beneficial to maintaining the stability of the battery structure. However, most polymers have a high degree of crystallinity at room temperature and poor segment mobility, so the room temperature conductivity is very low.

[0005] The most studied matrices in polymer electrolytes include ether polymers (polyethylene oxide, PEO), fluorine-containing polymers (polyvinylidene fluoride, PVDF; polyvinylidene fluoride-hexafluoropropylene, PVDF-HFP), carbonate polymers (polymethyl methacrylate, PMMA) and nitrile polymers (polyacrylonitrile, PAN). PEO is one of the most widely studied polymer matrices at this stage. Its advantages are low price and environmental protection. The PEO molecular chain segments have good flexibility, which is conducive to the rapid transmission of lithium ions. It is generally believed that the fluidity of cation transmission is related to the movement of the complex chain segments of the PEO chain.

[0006] Because ion transport relies on segmental motion of the backbone, this motion rapidly decreases with decreasing temperature and increasing crystallinity. Due to the presence of crystalline domains, the PEO-lithium salt system provides relatively low ionic conductivity (10 -7 S cm -1 ). Therefore, it is crucial to reduce the crystallinity of PEO to promote segmental motion, and the continuous motion of amorphous segments above the glass transition temperature (Tg) plays a decisive role in ion transport. In addition, the increase in the amorphous region of the PEO host with increasing temperature can improve the ionic conductivity and even the interfacial stability with electrode materials. However, operation at high temperatures may lead to the degradation of mechanical properties and a limited electrochemical stability window, resulting in lithium dendrite growth and reducing the safety performance of polymer electrolyte systems.

[0007] There are two urgent issues that need to be addressed for PEO electrolytes. On the one hand, the high crystallinity at room temperature leads to poor conductivity, while the mechanical properties are poor at high temperatures. On the other hand, PEO-based solid electrolytes have a narrow electrochemical window and lack stability under high voltage, which limits the application of PEO in high-voltage solid-state batteries. Summary of the invention

[0008] The purpose of the present invention is to provide a modified MOFs filler, a preparation method and a composite solid electrolyte for a lithium ion battery. After the obtained modified MOFs filler is added to the composite solid electrolyte, the conductivity of the composite solid electrolyte can be effectively improved, and it has a wide electrochemical stability window, and the assembled lithium battery exhibits excellent discharge capacity.

[0009] In order to achieve the above object, the technical solution adopted by the present invention is:

[0010] A modified MOFs filler, wherein the MOFs filler refers to one of the following two types:

[0011] The first type: In the MIL series of MOF materials, some metal nodes are replaced by metal cerium;

[0012] The second type: MIL series MOF materials, and their surfaces contain holes formed by etching.

[0013] The metal is one of Fe, V, Cr and Ni.

[0014] The MIL series MOF material refers to one or more of MIL-53, MIL-68, MIL-88A, MIL-88B, MIL-100, MIL-101, and MIL-125.

[0015] The proportion of cerium in all metals is 0.1-0.45.

[0016] The pore size range is 10-200 nm.

[0017] The preparation method of the modified MOFs filler mentioned above, for the first filler, comprises the following steps: dissolving the metal source salt, the cerium salt and the ligand in water, and centrifuging, washing and drying after the crystallization reaction;

[0018] For the second filler, the following steps are included: dissolving the metal source salt and the ligand in water, centrifuging, washing and drying after crystallization reaction to obtain MOF particles; dispersing the prepared MOF particles and phytic acid in water, heating, washing, centrifuging and drying.

[0019] The ligand is fumaric acid, the metal source salt is FeCl3·6H2O, and the cerium salt is Ce(NO3)3·6H2O.

[0020] For the first filler, the molar ratio of the cerium salt to the metal source salt is in the range of (0.1-0.45); the ratio of the total molar amount of the metal source salt and the cerium salt to the molar amount of the added ligand is 1:(0.8-1.2);

[0021] The conditions for the crystallization reaction are: 60-90°C, 10-15h;

[0022] The drying conditions are: under vacuum conditions, 90-120°C, 20-48h.

[0023] For the second filler, the molar ratio of the metal source salt to the ligand is 1:(0.8-1.2);

[0024] The conditions for the crystallization reaction are: 60-90°C, 10-15h;

[0025] The drying conditions are: under vacuum conditions, 90-120°C, 20-48h.

[0026] Preferably, the addition ratio of MOF particles to phytic acid is (80-120) mg: (40-150) μl;

[0027] The heating conditions are: under vacuum, 80-110°C, 2-8h;

[0028] The drying conditions are: under vacuum conditions, 50-80°C, 4-9h.

[0029] A method for preparing a composite solid electrolyte comprises dispersing a modified MOFs filler prepared by any of the above methods in a solvent under the protection of an inert gas, adding an organic electrolyte lithium salt and PEO, stirring to obtain a colloidal suspension, and then pouring the mixture into a mold for drying and forming.

[0030] Preferably, the molar ratio of the organic electrolyte lithium salt to the EO in PEO is 1:(18-25); the organic electrolyte lithium salt is selected from lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4) or lithium bis(trifluoromethanesulfonyl)imide (LiN(CF3SO2)2).

[0031] The added amount of the modified MOFs filler is 5-20wt% of the total amount of PEO and the modified MOFs filler.

[0032] Preferably, the drying and molding conditions are: 50-70°C, 30-50h.

[0033] Application of the composite solid electrolyte prepared by any of the above methods in lithium-ion batteries.

[0034] The beneficial effects of the present invention are:

[0035] The cerium-doped MOF material is obtained by adding cerium salt during the preparation of MOF. The PEO-based composite solid electrolyte prepared by using the above material as filler has high mechanical strength, good thermal stability, a wide electrochemical stability window, improved interface performance, significantly improved ionic conductivity and Li + The transfer number is reduced, and the formation of dendritic lithium is significantly eliminated during the cycle; the assembled lithium battery exhibits excellent discharge capacity, coulombic efficiency and capacity retention rate;

[0036] At the same time, after the MOF is prepared, it is etched to obtain an etched MOF material. The PEO-based composite solid electrolyte prepared by using the above material as a filler has significantly improved ionic conductivity and Li + The transfer number is increased, and the electrochemical stability window is wider; the corresponding lithium batteries exhibit excellent discharge capacity and lower polarization. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1(a) MIL-88A; (b) MIL-88A0.1Ce; (c) MIL-88A0.2Ce; (d) SEM of MIL-88A0.1Ce; (e) XRD of MIL-88A and MIL-88AxCe;

[0038] Figure 2 (a) XPS spectra of MIL-88A and MIL-88AxCe; (b) Py-FTIR spectra;

[0039] Figure 3 (a) Surface SEM of PEO; (b) Cross-sectional SEM; (c) Surface SEM of MIL-88A@CSPE; (d) Cross-sectional SEM; (e) Surface SEM of MIL-88A0.2Ce@CSPE; (f) Cross-sectional SEM;

[0040] Figure 4 FTIR spectra of (a) MIL-88AxCe@CSPE and PEO; (b) FTIR spectra of MIL-88A@CSPE and MIL-88A; (c) FTIR spectra of MIL-88A0.2Ce@CSPE and MIL-88A0.2Ce;

[0041] Figure 5 (a) Comparison of stress-strain curves; (b) TG curves of MIL-88AxCe@CSPE and PEO; (c) DSC curves;

[0042] Figure 6 (a) Ionic conductivity of MIL-88A@CSPE with different MIL-88A loadings; (b) Ionic conductivity of MIL-88AxCe@CSPE and PEO; (c) Linear sweep voltammogram of MIL-88AxCe@CSPE and PEO at 60°C;

[0043] Figure 7 Ion migration numbers of different solid electrolytes at 60°C (a) PEO; (b) MIL-88A@CSPE;

[0044] (c)MIL-88A0.2Ce@CSPE;

[0045] Figure 8 Storage time dependence of resistance of different batteries at 60°C (a) PEO; (b) MIL-88A@CSPE;

[0046] (c) MIL-88A0.2Ce@CSPE; (d) Li||PEO||Li, Li||MIL-88A@CSPE||Li and

[0047] Li||MIL-88A0.2Ce@CSPE||Li battery at 60℃ and 0.1mA / cm 2 The charge and discharge voltage curve under

[0048] Fig. 9 (a) Rate performance and (b) cycling performance of full cells assembled with PEO, MIL-88A@CSPE and MIL-88A0.2Ce@CSPE at 60°C.

[0049] Fig.10 SEM of (ab) MIL-88A; (cd) MIL-88A-50μl; (ef) MIL-88A-100μl;

[0050] Fig.11 TEM of (ab) MIL-88A; (cd) MIL-88A-50μl; (ef) MIL-88A-100μl;

[0051] Fig.12 (ab) SEM of PEO; (cd) SEM of PEO-MIL-88A; (ef) SEM of PEO-MIL-88A-50μl; (gh) SEM of PEO-MIL-88A-100μl;

[0052] Fig.13 is the ionic conductivity of the composite solid electrolyte;

[0053] Fig.14 (a) Linear sweep voltammograms of full cells assembled for PEO, PEO-MIL-88A, PEO-MIL-88A-50μl and PEO-MIL-88A-100μl at 60°C; (b) rate performance. DETAILED DESCRIPTION

[0054] Composite solid electrolytes are usually composed of polymer matrix, inorganic filler, lithium salt and ionic liquid additives. The introduction of inorganic fillers into polymer electrolytes makes it possible to obtain composite polymer electrolytes with high ionic conductivity and high mechanical strength at the same time. The reason for the improvement of ionic conductivity is mainly that the addition of fillers reduces the crystallinity of PEO, enhances the interface stability, and promotes the dissociation of lithium salts, thereby increasing the lithium ion concentration in the electrolyte. Each material in the composite material retains its own properties, so the addition of fillers can significantly improve the mechanical properties of the electrolyte.

[0055] MOFs are a class of materials with regular pore structures, large specific surface areas, and both organic and inorganic properties. They have been widely used in a variety of fields. Recently, MOFs have become a hot research direction in polymer electrolytes due to their insulation and inherent properties. Based on factors such as MOFs composition, structure, and internal environment, it is possible to achieve high-performance polymer electrolytes. MOFs have high surface polarity and can control the Lewis acid-base interaction in the system, thereby improving its electrochemical performance. Secondly, due to the diverse structures of MOFs, they can adapt to different materials, which makes it easy for MOFs to be composited with different electrolyte materials and use their excellent electrochemical properties to modify solid electrolytes, thereby improving the ionic conductivity, ion migration and other electrochemical properties of solid electrolytes.

[0056] In the present invention, the performance of PEO is optimized by MOFs filler modification. First, a series of bimetallic MIL-88A materials are prepared by Ce doping (also known as substitution) and used as fillers. MIL-88A materials with different Ce doping amounts show different Lewis acidities. Experiments show that the ionic conductivity and electrochemical properties of PEO solid electrolytes are positively correlated with the Lewis acidity of MOF. The solid electrolyte prepared by MIL-88A0.2Ce has the highest Lewis acidity, with a maximum ionic conductivity of 4.47×10 - 4 Scm -1 On the other hand, defect sites of MOFs can be constructed by acid etching to expand the active sites of MOFs. High specific surface area, high porosity and high thermal stability are conducive to the entry of ions into the Lewis acid centers on the inner surface of MOF. These sites have strong Lewis acid-base interactions with the ether oxygen (EO) bonds of PEO and the anions of Li salts, producing higher Li + The CSPE has a transfer number and conductivity of 4.7×10 at 60°C. -4 S cm -1 High ionic conductivity.

[0057] Comparative Example 1: Synthesis of MIL-88A

[0058] 6.67mmol of ferric chloride hexahydrate (FeCl3·6H2O) and 6.67mmol of fumaric acid were dissolved in 25ml of ultrapure water respectively. The above salt solutions were mixed in a polytetrafluoroethylene reactor and stirred for 5 minutes. Then the crystallization reaction was carried out at 70°C for 12h. Finally, the precipitated powder was collected by centrifugation, washed several times with ethanol, and then dried at 100°C under vacuum for 24h to obtain MIL-88A.

[0059] Example 1 Synthesis of MIL-88AxCe

[0060] Ce-doped MIL-88A (labeled as MIL-88AxCe, where x represents the substitution ratio) was prepared by partial replacement. MIL-88A0.2Ce was prepared by the same protocol except that 1.3 mmol of cerium nitrate hexahydrate (Ce(NO3)3·6H2O) was added to replace an equal amount of FeCl3·6H2O. Other doped MIL-88A catalysts, including MIL-88A0.1Ce and MIL-88A0.3Ce, were also prepared with different Ce substitution ratios.

[0061] Characterization of MIL-88A and MIL-88AxCe

[0062] Scanning electron microscope (SEM) image ( Figure 1 The ad area in the middle shows that both MIL-88A and MIL-88A0.2Ce are rod-shaped with a relatively uniform length distribution of about 10 μm. The morphology of MIL-88A does not change significantly after Ce doping. The crystal structures of the original and Ce doped MIL-88A were analyzed by XRD, as shown in Figure 2. Figure 1 As shown in the middle e area. The original MIL-88A shows two different peaks at 10.4° and 12.1°, corresponding to the (101) and (002) crystal planes, respectively, which is consistent with the standard card characteristic peaks of MIL-88A. As for the XRD pattern of MIL-88AxCe, it can be observed that the peak of the (101) crystal plane moves to a higher angle. In addition, the peak of the (101) plane gradually widens and splits into two peaks. Its intensity changes significantly with the increase of the Ce substitution ratio. This is due to the long-range distortion / destruction of MIL-88A and the formation of crystal defects caused by Ce doping.

[0063] XPS tests were carried out to further analyze the chemical composition and electronic structure of MIL-88A and MIL-88AxCe. Figure 2 In the a region, it can be seen that among all prepared MOF materials, at about 725 eV (Fe 2p 1 / 2 ), 716eV (satellite) and 712eV (Fe 2p 3 / 2 ) at the binding energy (BE) of Fe(III). As the Ce doping content increases, all the peaks of Fe 2p and O1s in the XPS spectrum shift slightly to a lower BE. This indicates that the Ce-O-Fe bond is formed by Ce doping because Ce has a lower electronegativity than Fe. Combining the results of XRD and XPS, Ce(III) was successfully doped into MIL-88A and formed Ce-O-Fe in the node. Pyridine infrared tests were also carried out. In the Py-FTIR spectrum ( Figure 2The pyridine molecule coordinated to a tetrahedrally unsaturated metal site (Ce or Fe center) in region b is at ~1069 cm -1 and ~1040cm -1 The two obvious peaks of the band prove the existence of Lewis acid sites.

[0064] The Lewis acidity (i.e., the amount of LAS, labeled LA) of each MOF was calculated according to the formula. The amount of LAS of MIL-88A and MIL-88AxCe is summarized in Table 1. When the Ce substitution amount increases to 0.20, the number of strong acid sites increases steadily, and the acidity begins to decrease after further substitution.

[0065] Table 1 Lewis acidity of MIL-88A and MIL-88AxCe

[0066]

[0067]

[0068] Preparation of PEO-based composite solid electrolyte

[0069] The PEO-based composite SPE (labeled as MIL-88AxCe@CSPE) was obtained by solution casting. PEO (molecular weight = 6×10 6 ) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI). First, MIL-88A was ultrasonically treated in acetonitrile for 30 minutes. Then, LiTFSI was added to the above MOF dispersion and stirred for 2 hours, and then PEO was dissolved in the above suspension and stirred for 24 hours. The homogenized colloidal suspension was poured into a polytetrafluoroethylene mold and dried at 60°C for 48 hours to form a CSPE film. The mass percentage of MIL-88A, MIL-88A0.1Ce, MIL-88A0.2Ce and MIL-88A0.3Ce in the total amount of PEO and MOF was 10wt%, and the molar ratio of Li / EO was 1:20. All preparation processes were carried out in an argon-filled glove box.

[0070] Composite solid electrolyte characterization

[0071] SEM images of pure PEO solid electrolyte and composite solid electrolyte Figure 3 As shown in Figure 2, the prepared composite solid electrolyte is translucent, independent and bendable. The composite solid electrolyte can also adhere firmly to the electrode. Figure 3 As shown in region c, the interface resistance is reduced due to its smooth and flat surface. Figure 3The cross-sectional SEM of the composite solid electrolyte in the middle d region shows a thickness of about 50 μm, in which the MOF particles are evenly distributed in the PEO polymer. Figure 3 The middle cf region) is relatively flat without many defects or aggregations.

[0072] The crystallinity of PEO has a significant effect on the ionic conductivity of PEO-based solid electrolytes. By analyzing the XRD data of the prepared CSPE ( Figure 4 In the XRD pattern of PEO, there are two obvious peaks at 19.5° and 23.6°, which are assigned to the (120) and (112) crystal planes, respectively. After adding MIL-88AxCe, the relative intensity and width of these PEO characteristic peaks change to a certain extent. The peak intensity of the characteristic peaks decreases with the increase of Lewis acidity of the added MOF. These changes indicate that MIL-88AxCe can interact with the PEO matrix and increase its amorphous degree, which is beneficial to the transport of lithium ions in the electrolyte.

[0073] The structure of CSPE was further characterized by FTIR test ( Figure 4 First, at 1396cm -1 The peak near corresponds to the symmetric stretching of C=O, which can be observed in the FTIR spectra of both MIL-88A and MIL-88A@CSPE, confirming the presence of MIL-88A in MIL-88A@CSPE. Figure 4 In the middle b area, 1356 and 1346 cm -1 The peak at 1144, 1113 and 1061 cm -1 The peak at 1356 cm-1 belongs to the stretching of -COC-. It is worth noting that this bending doublet of -CH2- and the stretching ternary peak of -COC- are considered to be related to crystalline PEO. With the addition of MIL-88A, the bending vibration of -CH2- is only at 1356 cm-1. -1 A peak appears at 100°, with a reduced intensity, and the intensity of the tensile ternary peak -COC- is weakened. It clearly proves that the addition of MIL-88A destroys the crystallinity of PEO. Finally, all the characteristic peaks in the spectrum of MIL-88AxCe@CSPE are similar to those of PEO electrolyte.

[0074] Mechanical strength is an important goal of electrolyte membranes, and due to the addition of MOFs, the mechanical strength has also been effectively improved. Tensile strength test results ( Figure 5Area a in the middle shows that the maximum strength of the PEO electrolyte membrane is 1.29MPa, while the maximum strength of MIL-88A@CSPE and MIL-88A0.2Ce@CSPE can be increased to 2.93 and 3.83MPa, respectively. The enhancement of mechanical strength is attributed to the physical crosslinking between the active surface of MIL-88A and the PEO chain. When the polymer chain is subjected to external force, MIL-88A can act as a crosslinking point to disperse and transfer the stress to other polymer chains, thereby reducing stress concentration and increasing the strength of the polymer. This high mechanical strength property gives the composite electrolyte an advantage in inhibiting the growth of lithium dendrites when applied to metal lithium batteries.

[0075] The thermal stability of solid polymer electrolytes is one of the most important parameters in practical applications. Thermogravimetric analysis (TG) ( Figure 5 Area b in the middle shows that the thermal decomposition temperature of PEO is about 373.6°C, and the temperature increases slightly with the increase of the doping amount of MIL-88AxCe. Decomposition of PEO can be observed at around 350°C, and the final residual amount remains at ~3.3wt%. When the temperature rises to 600°C, the residual amount of MIL-88AxCe@CSPE is higher than that of PEO. The results show that the introduction of MIL-88AxCe particles can slightly improve the thermal stability of the electrolyte. Differential scanning calorimetry (DSC) measurements were performed to study the glass transition and crystallinity ( Figure 5 Figure 3 (c region in the middle). It can be seen that the addition of MIL-88AxCe to PEO reduces the glass transition temperature from -32°C to -34°C, indicating that MIL-88AxCe disordered the PEO chains, thereby reducing the crystallinity of CSPE. This means that MIL-88AxCe@CSPE has much more amorphous regions than PEO. The increase in amorphization will enhance the segmental motion of PEO chains.

[0076] Electrochemical performance test

[0077] In order to study the effect of MIL-88AxCe on the ion transport behavior of PEO-based CSPE, the ionic conductivity of MIL-88A@CSPE with different MIL-88A loadings was first tested by electrochemical impedance spectroscopy (EIS) in the temperature range of 30 to 80 °C. Figure 6 The optimal MOF loading was determined to be 10%. The ionic conductivity of MIL-88AxCe@CSPE at 30-80°C was then tested ( Figure 6The ionic conductivity of MIL-88AxCe@CSPE increases with the increase of Ce doping amount and then decreases, reaching the maximum value at x = 0.2. Similarly, the results show that the ionic conductivity of CSPE increases with the increase of Lewis acidity. The ionic conductivity of MIL-88A0.2Ce@CSPE at 60 ° C can reach 4.47×10 -4 Scm -1 , which is higher than the ionic conductivity of PEO (1.63×10 -4 S cm -1 ) is about 2 orders of magnitude higher.

[0078] Electrochemical stability is a key factor in evaluating the performance of solid polymer electrolytes and their practical application possibilities in batteries. The effect of MIL-88AxCe on the electrochemical stability window of CSPE was investigated by linear sweep voltammetry (LSV) measurements. Figure 6 As shown in the c area. From the LSV curves of SS||PEO||Li and SS||MIL-88AxCe@CSPE||Li measured at 60°C, it is observed that the latter shows a more stable voltage than the former, which means that the electrochemical stability of the PEO-based solid electrolyte is enhanced by adding MIL-88AxCe. The improvement in the electrochemical stability window is attributed to the effective capture ability of MIL-88AxCe for small molecules and the strong interaction between MIL-88AxCe nanoparticles and PEO chains.

[0079] In order to characterize Li + The effect on the total ionic conductivity was measured by impedance potentiostatic polarization analysis after polarization at 10 mV for 4000 s. Li+ ),like Figure 7 The ac region is shown in the figure. + Only 0.25, while the tLi of MIL-88A@CSPE + Increased to 0.49. Li+ The enhancement can be attributed to the Lewis acid-base interaction between MOFs and PEO which increases the concentration of mobile lithium ions.

[0080] In addition, the Li||SPE||Li symmetric cell was stored at 60 °C for 6 days ( Figure 8 The interfacial stability of PEO-based SPE was further investigated in the middle ac region. The initial resistance was much higher than that after high-temperature storage, which is because the thermal treatment can effectively improve the contact between Li and SPE. In addition, compared with PEO, MIL-88AxCe@CSPE has much less interfacial reaction with lithium, which is due to the strong affinity of MIL-88AxCe for small molecules, which can effectively absorb trace solvents or small molecules in the homogeneous nanocomposite polymer electrolyte membrane.

[0081] At 0.1 mA / cm 2 The long-term lithium plating / stripping performance of the Li||SPE|||Li symmetric cell was further characterized at 40°C and 60°C. Figure 8 The symmetric Li||MIL-88A@CSPE||Li battery operates for more than 450 hours, which is much longer than the Li|PEO||Li battery (only 120 hours before short circuit). The above results indicate that MIL-88A@CSPE has a stronger ability to inhibit the growth of lithium dendrites than PEO.

[0082] The prepared CSPE has high mechanical strength, good thermal stability, a wide electrochemical stability window, improved interfacial properties, significantly enhanced ionic conductivity and Li + The transfer number is significantly increased, and the formation of lithium dendrites during cycling is significantly eliminated. In particular, thanks to the high Lewis acidity of MIL-88AxCe, the prepared MIL-88AxCe@CSPE also shows significantly enhanced ionic conductivity and Li + Number of transfers.

[0083] To further evaluate the electrochemical performance of MIL-88AxCe@CSPE, LFP||SPE|||Li cells were assembled and tested at 60 °C. Fig. 9 Region a in the middle shows the rate performance of LFP||PEO||Li and LFP||MIL-88AxCe@CSPE||Li full cells. As shown in the figure, the discharge capacities of LFP||PEO||Li batteries at 0.05, 0.1, 0.2, 0.5, 1, and 2C rates are 158.3, 157, 153.2, 144.7, 118.6, and 56.9 mAh g -1 , while LFP||MIL-88AxCe@CSPE|Li battery has higher discharge capacity. High ionic conductivity and tLi + The polarization effect inside the battery can be alleviated, thereby reducing the increase in the polarization voltage inside the battery. Specifically, MIL-88A0.2Ce@CSPE has the highest ionic conductivity, providing 127.5 mAh g at 2C. -1 When the current density returned to 0.1C, the LFP||MIL-88A0.2Ce@CSPE||Li battery also showed a higher discharge capacity than the LFP||PEO||Li battery. Similarly, the cycle performance of the full battery was tested, such as Fig. 9 In the initial cycle, it can be observed that the discharge capacity of the battery increases due to the activation process. After 100 cycles, LFP||MIL-88A0.2Ce@CSPE||Li remains at 113.3 mAh g-1 For LFP||PEO||Li battery, the discharge capacity is only 76.6mAh g -1 During cycling, LFP||MIL-88A0.2Ce@CSPE||Li has a significant improvement in terms of stable electrode / electrolyte interface and lower interfacial reaction compared to LFP||PEO||Li. From the above results, LFP||MIL-88A0.2Ce@CSPE||Li exhibits excellent discharge capacity, coulombic efficiency and capacity retention.

[0084] Example 2 Synthesis of Etched MIL-88A

[0085] Take 100 mg of the synthesized MIL-88A and 50 μl of phytic acid and disperse them in 25 ml of water, transfer them to a 50 ml screw-on glass bottle after ultrasonic and stirring. Heat them in a vacuum oven at 90 ° C for 3 hours, and cool them naturally to room temperature to obtain a light orange product. Wash the product with water and ethanol respectively, and centrifuge it twice to obtain a relatively pure product. Finally, place the product in a vacuum oven at 60 ° C and dry it for 6 hours to obtain the modified MIL-88A-50 μl.

[0086] Characterization of MIL-88A and Etched MIL-88Ax

[0087] Scanning electron microscopy images of raw MIL-88A, 50 μl phytic acid etched MIL-88A, and 100 μl phytic acid etched MIL-88A were taken (see Fig.10 ), the surface of the unetched MOF material is denser, and with the increase of the amount of phytic acid, holes begin to appear on the material surface.

[0088] Further analysis of its structure, in the TEM image ( Fig.11 ), the MOF structure was not significantly damaged, and increasing the acidity could increase the number of etched holes without destroying the overall basic skeleton.

[0089] Preparation of PEO-based composite solid electrolyte

[0090] The PEO-based composite SPE was obtained by solution casting. PEO (molecular weight = 6 × 10 6) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI). First, MIL-88A was ultrasonically treated in acetonitrile for 30 minutes. Then, LiTFSI was added to the above MOF dispersion and stirred for 2 hours, and then PEO was dissolved in the above suspension and stirred for 24 hours. The homogenized colloidal suspension was poured into a polytetrafluoroethylene mold and dried at 60°C for 48 hours to form a CSPE film. The mass percentage of MIL-88A and etched MIL-88A in the total amount of PEO and MOF was 10wt%, and the molar ratio of Li / EO was 1:20. All preparation processes were carried out in a glove box filled with argon.

[0091] Composite solid electrolyte characterization

[0092] The composite electrolyte was obtained by combining acid-etched MIL-88A with PEO and LiTFSI. Surface and cross-sectional SEM images of CSPE ( Fig.12 ) shows the morphology and structure of the electrolyte. Compared with the rough surface of the PEO sample, the introduction of MIL-88A and modified MIL-88A made the surface of all composite electrolytes relatively smoother. From the SEM images, the MOFs were tightly encapsulated by the PEO matrix, and there were no obvious cracks or pinholes on the electrolyte surface, indicating a high affinity between MIL-88A and PEO. The SEM cross-sectional image shows the dense structure of the prepared composite solid electrolyte, and the MOFs are uniformly distributed in the PEO matrix. Further verification confirmed that the film thickness was about 50μm.

[0093] Electrochemical performance test

[0094] In order to investigate the effect of acid-etched MIL-88A on the ion transport behavior of PEO-based CSPE, the ionic conductivity of the composite solid electrolyte at 30-80 °C ( Fig.12 ). The ionic conductivity of CSPE increases with the degree of MOF acid etching. The ionic conductivity of MIL-88A-100μL-PEO at 60℃ can reach 4.7×10 -4 S cm -1 , which is higher than the ionic conductivity of PEO (1.63×10 -4 S cm -1 ) is about 2 orders of magnitude higher. The high ionic conductivity of MIL-88A-100μL-PEO is attributed to the capture of anions (TFSI) by MIL-88AMOF after etching. - ) capacity and the decrease in electrolyte crystallinity after addition.

[0095] The effect of etching MIL-88A on the electrochemical stability window of CSPE was studied by linear sweep voltammetry (LSV). Fig.13). Compared with PEO with a stable voltage of ~5.2V, MIL-88A-PEO and etched MIL-88A-PEO exhibited a wider electrochemical window (~5.6V), which means that the electrochemical stability of the electrolyte is improved. The significant improvement in the electrochemical stability window is due to the effective capture ability of MIL-88A for small molecules and the strong interaction between MIL-88A nanoparticles and PEO chains. The additional pores of the etched modified MIL-88A further adsorbed organic molecules.

[0096] LFP||SPE||Li cells were assembled and tested at 60 °C to investigate the electrochemical cycling and rate performance. Fig.14 It can be seen that the LFP||PEO||Li battery shows 158.3, 157, 153.2, 144.7, 118.6, and 56.9 mAh g at 0.05, 0.1, 0.2, 0.5, 1, and 2 C, respectively. -1 All LFP||etched MIL-88A-PEO||Li cells have higher discharge capacity and lower polarization than LFP||PEO||Li cells. Specifically, the etched MIL-88A-100μL-PEO with the highest ionic conductivity delivered 138.1mAh g at 2C. -1 When the current density returned to 0.1C, the LFP||etched MIL-88A-100μL-PEO||Li battery also showed a higher discharge capacity than the LFP||PEO||Li battery (150.8mAhg -1 ) Higher 157.2mAh g -1 The results show that the LFP||etched MIL-88A-100μL-PEO||Li full battery has good transport kinetics.

[0097] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.

Claims

1. A modified MOFs filler, characterized in that: The MOFs filler refers to one of the following two types: The first type: In the MIL series of MOF materials, some metal nodes are replaced by metal cerium; The second type: MIL series MOF materials, and their surfaces contain holes formed by etching.

2. The modified MOFs filler according to claim 1, characterized in that: The metal is one of Fe, V, Cr and Ni; The MIL series MOF material refers to one or more of MIL-53, MIL-68, MIL-88A, MIL-88B, MIL-100, MIL-101, and MIL-125.

3. The modified MOFs filler according to claim 1, characterized in that: The proportion of cerium in the total metal is 0.1-0.45; the pore size range is 10-200nm.

4. The method for preparing the modified MOFs filler according to any one of claims 1 to 3, characterized in that: The first filler comprises the following steps: dissolving the metal source salt, the cerium salt and the ligand in water, and centrifuging, washing and drying after the crystallization reaction; For the second filler, the following steps are included: dissolving the metal source salt and the ligand in water, centrifuging, washing and drying after crystallization reaction to obtain MOF particles; dispersing the prepared MOF particles and phytic acid in water, heating, washing, centrifuging and drying.

5. The preparation method according to claim 4, characterized in that: The ligand is fumaric acid, the metal source salt is FeCl3·6H2O, and the cerium salt is Ce(NO3)3·6H2O.

6. The preparation method according to claim 4, characterized in that: For the first filler, the molar ratio of the cerium salt to the metal source salt is in the range of (0.1-0.45); the ratio of the total molar amount of the metal source salt and the cerium salt to the molar amount of the added ligand is 1:(0.8-1.2); The conditions for the crystallization reaction are: 60-90°C, 10-15h; the conditions for drying are: under vacuum conditions, 90-120°C, 20-48h.

7. The preparation method according to claim 4, characterized in that: For the second filler, the molar ratio of the metal source salt to the ligand is 1:(0.8-1.2); The conditions for the crystallization reaction are: 60-90°C, 10-15h; the conditions for drying are: under vacuum conditions, 90-120°C, 20-48h.

8. The preparation method according to claim 7, characterized in that: The addition ratio of MOF particles and phytic acid was (80-120) mg: (40-150) μl; The heating conditions are: 80-110℃, 2-8h under vacuum conditions; the drying conditions are: 50-80℃, 4-9h。 9. A method for preparing a composite solid electrolyte for lithium-ion batteries, comprising dispersing the modified MOFs filler according to any one of claims 1 to 3 in a solvent under the protection of an inert gas, adding an organic electrolyte lithium salt and PEO, stirring to obtain a colloidal suspension, and then pouring it into a mold to dry and shape it.

10. The preparation method according to claim 9, characterized in that: The molar ratio of the organic electrolyte lithium salt to the EO in PEO is 1:(18-25); the amount of the modified MOFs filler added is 5-20wt% of the total amount of PEO and the modified MOFs filler; the organic electrolyte lithium salt is selected from lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4) or lithium bis(trifluoromethanesulfonyl)imide (LiN(CF3SO2)2).

Citation Information

Patent Citations

  • Preparation method of rod-like cerium-doped MIL-53 (Fe) material

    CN110128671A

  • MXene (at) Ce-MOF material rich in oxygen vacancies, preparation method of MXene (at) Ce-MOF material and application of MXene (at) Ce-MOF material in supercapacitor

    CN115274308A

  • Fluorinated two-dimensional inorganic nanofiller reinforced PEO-based solid polymer electrolyte, and preparation method and application thereof

    CN117438661A

  • Composite fiber paper-based self-supporting positive electrode material and preparation method thereof, lithium-sulfur battery positive plate and lithium-sulfur battery

    CN118039841A

  • Hollow metal organic framework ion conduction composite membrane, preparation method and application

    CN118431500A

Cited By

  • Cerium-doped modified MOFs-based composite solid electrolyte and preparation method and application thereof

    CN122455903A